PERANCANGAN SISTEM LATIHAN SOAL DAN UJIAN TOEIC (TEST OF ENGLISH FOR INTERNATIONAL COMMUNICATION) BERBASIS WEB UNIVERSITAS WIDYATAMA - Frans Geraldo Simangusong; Ai Rosita (Jurnal Darma Agung, 2022)
TOEIC which stands for Test Of English for International Communication is one of the well-known English proficiency tests and can be an indicator of participants' ability to use English. In general, this test is divided into two parts, namely listening and reading comprehension tests, where participants fill in their answers on an answer sheet according to the questions they hear in voice and writing. Media The formulation of the problem described in this study is how to build an online and web-based TOEIC exam application so that it can optimize exam and learning activities through TOEIC exercises to be more flexible, effective, and efficient. The focus of the research is how to optimize the evaluation and assessment process. In this case, it makes it easier for performance management (administrators) to make questions, streamline time for correcting answers and examinees know the results quickly, precisely, and accurately. The test results show that the application of practice questions and web-based TOEIC can process data that has been inputted by the administrator and presented to participants in following performance standards in general. The test results can also be used to provide a quick assessment and analyze the results of the scoring system assessment. Suggestions that can be put forward for the development and improvement of this web-based TOEIC test are to think of a better input mechanism to make it easier for users to process data input problems.